Penerapan Terapi Psikoreligius Dzikir Terhadap Kontrol Halusinasi Pada Asuhan Keperawatan Pasien Dengan Halusinasi Pendengaran DiRumah Sakit Madani Palu - Halisa Karadjo; Agusrianto Agusrianto (Madago Nursing Journal, 2022)
Introduction : Schizophrenia is a major disorder in thought processes and disharmony between thought processes, affect and emotions. Schizophrenia has the main symptom of decreased sensory perception, namely hallucinations. Hallucinations consist of several kinds, one of which is auditory hallucinations. Auditory hallucinations are hearing voices or complete conversations between two or more people in which the client is asked to do something. The purpose of this study was to apply psychoreligious dhikr therapy to the control of hallucinations in the care of patients with auditory hallucinations at Madani Hospital Palu. Research method: Descriptive research with a case study approach. Results: Respondents were able to control hallucinations by rebuking hallucinations, conversing with other people, performing scheduled activities especially psychoreligious therapy and teaching patients to take medication correctly independently, when evaluating the patient said he could control hallucinations independently. Conclusion: The application of dhikr psychoreligious therapy can control hallucinations in hallucinating patients at Madani Hospital Palu.